Development of Engineered CAR T Cells Targeting Tumor-Associated Glycoforms of MUC1 for the Treatment of Intrahepatic Cholangiocarcinoma. Issue 3 (8th April 2023) - Mao, Li; Su, Sheng; Li, Jia; Yu, Songyang; Gong, Yu; Chen, Changzhou; Hu, Zhiqiang; Huang, Xiaowu
Abstract : Intrahepatic cholangiocarcinoma (ICC) is a common malignancy arising from the liver with limited 5-year survival. Thus, there is an urgency to explore new treatment methods. Chimeric antigen receptor T (CAR T) cell therapy is a very promising cancer treatment. Though, several groups have investigated CAR T cells targeting MUC1 in solid cancer models, Tn-MUC1-targeted CAR T cells have not yet to be reported in ICC. In this study, we confirmed Tn-MUC1 as a potential therapeutic target for ICC and demonstrated that its expression level was positively correlated with the poor prognosis of ICC patients. More importantly, we successfully developed effective CAR T cells to target Tn-MUC1-positive ICC tumors and explored their antitumor activities. Our results suggest the CAR T cells could specifically eliminate Tn-MUC1-positive ICC cells, but not Tn-MUC1-negative ICC cells, in vitro and in vivo. Therefore, our study is expected to provide new therapeutic strategies and ideas for the treatment of ICC.